Testing volatility on the Trinidad and Tobago stock exchange - Leon, Hyginus (2000)
Estimates the responsiveness of sectoral subindex returns to changes in the domestic market portfolio. Compares predictions of nonsystematic risk using GARCH and EGARCH specifications of the error variance.